Evolution of the human immunodeficiency virus type 1 subtype-specific V3 domain is confined to a sequence space with a fixed distance to the subtype consensus. - Lukashov, V V (1997)
Human immunodeficiency virus type 1 (HIV-1) strains can be separated into genetic subtypes based on phylogenetic analysis of the envelope gene. Once it had been shown that population-wide intrasubtype genetic variation of HIV-1 strains increases in the course of the AIDS epidemic, it remained uncertain whether HIV-1 subtypes are phenotypic entities spreading as distinct virus populations. To examine this, we applied Eigen's concepts of sequence geometry and fitness topography to the analysis of intrasubtype evolution of the gp120 V3 domain of HIV-1 subtypes A, B, C, and D in the course of the global AIDS epidemic. We observed that despite the high evolution rate of HIV-1, the nonsynonymous distances to the subtype consensus of sequences obtained early in the epidemic are similar to those obtained more than 10 years later, in contrast to the synonymous distances, which increased steadily over time. For HIV-1 subtype B, we observed that the evolution rate of the individual sequences is independent of their distance from the subtype B consensus, but for the individual sequences most distant from the consensus evolution away from the consensus is constrained. As a result, individual HIV-1 genomes fluctuate within a sequence space with fixed distance to the subtype consensus. Our findings suggest that the evolution of the V3 domain of HIV-1 subtypes A, B, C, and D is confined to an area in sequence space within a fixed distance to the consensus of a respective subtype. This in turn indicates that each HIV-1 subtype is a distinct viral quasispecies that is well adapted to the present environment, able to maintain its identity in the V3 region over time, and unlikely to merge during progression of the AIDS epidemic.